Kawasaki Disease in Children: A Brief Update - Rahman, Shahana A; Laila, Kamrul (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Kawasaki disease (KD) is a common acute vasculitis of childhood that may lead to coronary artery abnormalities in about 25% of patients if left untreated. KD is reported as the leading cause of acquired heart disease in children replacing rheumatic feverin developed countries. Strong epidemiological data are not available from developing countries, but it is increasingly recognized in rapidly industrializing countries of Asia including India,where it might has replaced rheumatic heart disease as the most common cause of acquired heart disease. This increasing recognition could be due to actual rise in number of KD cases or due to more diagnosis following increased awareness. The status of KD in Bangladesh is not known. But unpublished data from Bangabandhu Sheikh Mujib Medical University (BSMMU) show a sustained and significant increase in the number of KD cases over the years. The reasons for this increase may be similar to our neighbouring country India. Aetiology of KD still remains unknown. But there have been many hypotheses including infection, immune dysregulation, super-antigen and genetic factors. The diagnosis of KD is based on the presence of ≥ 5 days of fever and the presence of ≥4 of the 5 principal clinical features (1.Extremity Changes, 2. Conjunctival injection, 3.Oral changes 4.Exanthem/Rash, and 5. Lymphadenopathy). The diagnosis of KD may be very challenging for even a very experienced paediatrician. It must be considered in a child with prolonged fever, undue irritability and sequential appearance of principal clinical features. KD patients should be managed timely with intravenous immunoglobulin (IVIG) and aspirin in proper dose. It is to be remembered that KD is no longer considered as a one-time disease of childhood, as it can be associated with significant long term sequelae. J Bangladesh Coll Phys Surg 2024; 42: 68-77